Multispectral Remote Sensing to Delineate the Distribution Area of Scandium-Bearing Minerals in Bauxite Mining Sites, West Kalimantan Province, Indonesia (Rudarsko-geološko-naftni zbornik, 2023)
The rising demand for scandium led to massive exploration activities for its discovery from mining by-products. Therefore, this study attempts to delineate the distribution of scandium-bearing minerals in the surrounding bauxite mining area, Tayan District, West Kalimantan Province, Indonesia. Preliminary studies were conducted by applying optical sensors to discriminate the types of minerals, such as kaolinite, gibbsite, goethite, and quartz. The spectral information aids the reconnaissance study by providing data on specific rocks and minerals using the short-wave infrared (SWIR), processed into a series of bands with spectral ranges from 0.35 to 2.5 μm. The data was then compared with the structural lineament from the ALOS PALSAR imagery to infer the prospective area with the structural pattern. The integrated band math minerals and geochemical data taken from X-ray fluorescence and Inductively Coupled Plasma-Mass Spectrometry suggest that the Sc-bearing minerals were disseminated predominantly on the bauxite laterite profile from pyroxene diorite and diorite parent rock weathering. The spectral range for goethite as the Sc-bearing minerals is from 0.43 to 1.03 , with the main absorption features from 2.0 to. 2.4 . Furthermore, goethite is mainly concentrated at the top bauxite horizon associated with the structurally related hill. The ore-bearing minerals also occupied the tailing pond and some beneficiation areas in relatively minor proportion. This study is undoubtedly valuable for the practical need to support mineral exploration through remote predictive mapping.